Current status of transcutaneous auricular vagus nerve stimulation for tinnitus: a narrative review of modern research - Wu, Qiqi; Wang, Jiawei; Han, Dexiong; Qian, Lala; Hu, Hantong; Gao, Hong (Frontiers in Neuroscience, 2024)
Tinnitus, characterized by phantom sound perception, is a highly disruptive disorder lacking definitive and effective treatments. Its intricate neural mechanisms are not fully understood. Transcutaneous auricular vagus nerve stimulation (taVNS) has demonstrated potential as a substitute or supplementary treatment by activating central vagal pathways. However, standardized therapeutic protocols and objective tests to assess efficacy are lacking. Therefore, taVNS shows promise as a therapy for tinnitus, and treatment protocols should be optimized in future clinical trials.